Nimodipine as vasodilator in guide catheter flush to prevent vasospasm during endovascular stroke treatment - Sommer, Louisa J.; Jesser, Jessica; Nikoubashman, Omid; Nguyen, Thanh N.; Pinho, Joao; Reich, Arno; Wiesmann, Martin; Weyland, Charlotte S. (Clinical neuroradiology, 2024)
The clinical importance and management of vasospasm as a complication during endovascular stroke treatment (EVT) has not been well studied. We sought to investigate the effect of adding nimodipine to the guiding catheter flush (GCF) to prevent vasospasm during EVT.
Online veröffentlicht: 31. Mai 2024
Gesehen am 15.01.2025